Banana and plantain (Musa spp.) growth depends on size and physiological stage of planting material - Blomme, Guy; Swennen, Rony L.; Tenkouano, A. (2005)
The influence of the size and physiological stage of the sucker-derived planting material on subsequent root and shoot growth of banana and plantain has not been studied in detail. The objective of this study was to evaluate associations between traits of the sucker planting material and root and shoot traits of the sucker-derived plants for different Musa spp. genotypes. Sucker-derived plants of 2 plantain landraces: 'Bobby Tannap' and 'Obino l'Ewai' and 6 plantain-derived hybrids were assessed. Twenty suckers of different size and physiological stage were planted per genotype during early July 1998 and evaluation was done at 20 weeks after planting (WAP). The results indicate that sucker-derived plant growth depends not only on the physiological stage of the sucker planting material, but also on the corm size and genotype